The Role of Multimedia Coordinator and Reporter in Management of Enjoy Semarang Section in Tribun Jateng Website - Muhammad Irzal Adiakurnia; S. Rouli Manalu, Ph.D (Interaksi Online, 2017)
In the era of advance technology, Indonesia participates as one of the countries that has a great number of internet users with 88,1 million active users in 2016. Yahoo and Daylysocial.net also said that Indonesian internet users prefer to access information through internet rather than radio or newspaper. This phenomenon indicates that various mass media must be converged with online in order to be easily accessed by the users. Tribun Jateng as one of the media incorporated in Group of Regional Newspaper, Kompas Gramedia, has done its convergence with online media. Tribun Jateng has a website called jateng.tribunnews.com. There is a section in the website called Enjoy Semarang, but does not become a priority for Tribun Jateng editorial staff. That phenomenon can be seen from several evidences: the travel news which was not updated and some of them which were adapted from other media. Moreover, the number of its visitors is less than other sections in Tribun Jateng website. We, as the team of the research study, have evaluated that Enjoy Semarang is potential to share information and support the business of Tribun Jateng. This is supported by two reasons: the huge interest of travel news and the rapid evolving of tourism industry in Indonesia. We have worked together with Tribun Jateng to build Enjoy Semarang section, which then changed into travel section. We have applied a lot of innovations with regard to the concept of covering news, multimedia integration (infographic, travel videos, map, and photo gallery), new integration of social media, marketing, and business for the sections. For two months and 21 days, the result is the increase of page view until 12,263. There were 310 news, four infographics, 22 photo galleries, four videos, nine maps, 800 followers of Instagram and Line, and more than 1,000 comments on social media. As for business, we got two advertorials. We made a series of online and offline events to increase the awareness of the travel section from 27% to 75%. Today, online media has become the reference of the readers. High competition makes each media cannot ignore the technology updates because it can build the innovation of technology and the special characteristics of the media. In the implementation, the competition has pulled the journalistic practice so that it has shifted from its own ideal values. The essence of journalism as the resources and the educators has changed, and it more concerns with the entertainment. This has led to the large number of the readers so that the business profit becomes bigger.